2018
DOI: 10.3390/w10030332
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Constructed Wetlands for Water Quality Improvement in a Tea Estate Catchment: The Pussellawa Case Study

Abstract: Abstract:Water in agricultural catchments is prone to pollution from agricultural runoff containing nutrients and pesticides, and contamination from the human population working and residing therein. This study examined the quality of water in a drainage stream which runs through a congested network of 'line houses' (low-income housing, typically found arranged in straight 'lines' on estates) in the tea estate catchment area of Pussellawa in central Sri Lanka. The study evaluated the applicability of vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…It is important to note that not all studies used wetland plants [43,83,89] or identified the specific plant species within the wetland system [148,159,179]. Also, not all primary studies that specified the plant species present in the wetland system analyzed the impact of phytoremediation as a removal mechanism [21,173,205]. For the studies that did investigate phytoremediation, vegetated systems increased removal efficiencies compared to non-vegetated systems [51,55,66,95,154,161,175,181,217], with mature plants out-performing younger ones [158].…”
Section: Removal Mechanisms and Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that not all studies used wetland plants [43,83,89] or identified the specific plant species within the wetland system [148,159,179]. Also, not all primary studies that specified the plant species present in the wetland system analyzed the impact of phytoremediation as a removal mechanism [21,173,205]. For the studies that did investigate phytoremediation, vegetated systems increased removal efficiencies compared to non-vegetated systems [51,55,66,95,154,161,175,181,217], with mature plants out-performing younger ones [158].…”
Section: Removal Mechanisms and Efficienciesmentioning
confidence: 99%
“…Wetland treatment systems, including natural and constructed wetlands, are now being used extensively across the United States and the world to treat non-point source pollution. This is due to their cost-effectiveness and low energy consumption compared to other surface water treatment methods (e.g., coagulation, membrane filtration, ion exchange) [20][21][22]. Wetlands utilize plants, soils, and associated microbial assemblages to remove pollutants through biodegradation, substrate adsorption, and plant uptake [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The TSS removal process in HSSFCW is due to the deposition process caused by the interception of suspended solids because of the reduced speed of water flow through wetland media Vymazal et al, 1998; Wallace and Knight, 2006;Weerakoon et al, 2018). In fine-grained media, the interception process occurs randomly either at the micro scale (Brownian motion) or macro scale (bioturbation) which makes it easy for the particles to settle (Kadlec and Wallace, 2009;Vymazal et al, 1998).…”
Section: Effect Of the Technology Combination On Tssmentioning
confidence: 99%
“…The efficiency of the series-connected two-stage HSS-FCW treatment system showed a variable removal efficiency of TSS and COD, despite the significant influent fluctuations. Other studies also reported that the degradation and sedimentation of pollutants in the HSSFCW treatment system are mostly affected by hydraulic factors (i.e., HRT or HLR) and mass loading rate (Ghosh and Gopal 2010;Jinadasa et al 2013;Shuib and Baskaran 2015). Furthermore, the treatment efficiency of a HSSFCW system is dependent on the nature of the original wastewater supply, selection of media types, feeding mode, and aeration conditions (Stefanakis and Tsihrintzis, 2012).…”
Section: Pollutant Removal Efficiencymentioning
confidence: 99%
“…Many authors have also recommend that the UASB-CW integrated treatment system has a high potential to improve water quality (Badejo et al 2014;Raboni et al 2014), since the UASB reactor removes most of the organic matter (Morino-Solis et al 2015), reduces the large wetland area requirement (Alvarez et al 2008), avoids wetland clogging problems, and increases the life cycle of CW (Kyambadde et al 2005). While the CW further mitigates the remaining organics, solids, nutrients, and pathogens (Balleseros et al 2016;Jinadasa et al 2013), and heavy metals (Sedaqua 2013). Moreover, the application of this integrated treatment technology is promising for resource-limited countries due to its superior advantages mentioned elsewhere (Jamashidi et al 2014;Kyambadde et al 2005).…”
Section: Introductionmentioning
confidence: 99%